Legal nature of the acts of the Constitutional Court of the Republic of Belarus - Sinitsyna, Anna M. (Journal of the Belarusian State University. Law, 2019)
This article is a research of the legal nature of the acts of the Constitutional Court of the Republic of Belarus. Special attention is paid to the analysis of the judicial properties of the decisions and conclusions of the body of the constitutional justice and their legal force. The role of the Constitutional Court of the Republic of Belarus in lawmaking and improvement of national legislation is noted in the article as well.
Keywords: Constitutional Court of the Republic of Belarus; acts; judicial properties; legal nature; legal force